From PsO to PsA: the role of TRM and Tregs in psoriatic disease, a systematic review of the literature - Lobão, Bárbara; Lourenço, Diana; Giga, Ana; Mendes-Bastos, Pedro (Frontiers in Medicine, 2024)
Introduction: Psoriasis (PsO) is a chronic skin condition driven by immune meditaors like TNFα, INFγ, IL-17, and IL-23. Psoriatic arthritis (PsA) can develop in PsO patients. Although psoriatic lesions may apparently resolve with therapy, subclinical cutaneous inflammation may persist. The role of tissue-resident memory T-cells (TRM), and regulatory T cells (Tregs) is being explored in this context. This systematic review explores TRM and Tregs in psoriatic disease (PsD) and its progression. Methods: A systematic review, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, was performed using Pubmed® and Web of ScienceTM databases on June 3rd 2023, using patient/population, intervention, comparison, and outcomes (PICO) criteria limited to English language. Results: A total of 62 reports were identified and included. In PsO, chronic inflammation is driven by cytokines including IL-17 and IL-23, and cellular mediators such as CD8+ and CD4+ T cells. TRM contributes to local inflammation, while Tregs may be dysfunctional in psoriatic skin lesions. Secukinumab and guselkumab, which target IL-17A and the IL-23p19 subunit, respectively, have different effects on CD8+ TRM and Tregs during PsO treatment. Inhibition of IL-23 may provide better long-term results due to its impact on the Treg to CD8+ TRM ratio. IL-23 may contribute to inflammation persisting even after treatment. In PsA, subclinical enthesitis is perceived as an early occurence, and Th17 cells are involved in this pathogenic process. Recent EULAR guidelines highlight the importance of early diagnosis and treatment to intercept PsA. In PsA, CD8+ TRM cells are present in synovial fluid and Tregs are reduced in peripheral blood. The progression from PsO to PsA is marked by a shift in immune profiles, with specific T-cells subsets playing key roles in perpetuating inflammation. Ongoing studies such as IVEPSA and PAMPA aim to improve our knowledge regarding PsA interception in high-risk PsO patients, emphasizing the need for further research. Conclusion: Early intervention is crucial for PsO patients at high risk of PsA; T cells, particularly type 17 helper T cells, and CD8+ cells are key in the progression from PsO-to-PsA. Early targeting of TRM in PsD shows promise but more research is needed.